A Contribution of the Development of the Social Studies Senior Preservice Teachers: Ethics of the Teaching Profession - Akhan, Nadire Emel; Öztürk, Ahmet (Fırat University, 2022)
The aim of this study is to contribute to the professional development of the pre-service teachers of social studies teaching by implementing practices of ethics of the teaching profession. This study was conducted with 55 preservice teachers studying in the final year of the social studies teaching department at the education faculty of a state university in Turkey in the fall semester of 2019-2020 academic year. School wide action research, a type of action research, which is one of the qualitative research methods, was used in the research. In the application stage of the study, an “ethics of the teaching profession seminar” was conducted by the researchers for 10 weeks. A questionnaire developed by researchers in line with expert opinions was used as a data collection tool in the study. The collected data were analyzed with the descriptive analysis method. When we evaluate the results of the research in general, it is possible to say that practices of the ethics of teaching profession make positive contributions to the preservice teachers' ethical principles, increase their professional, personal and social development as individuals, and develop their sense of responsibility regarding the principles of professional ethics. Accordingly, it is recommended that applications be planned to enable teachers and preservice teachers to be aware of the principles of teaching professional ethics, adopt these principles and take the responsibilities required by their profession.

Bu çalışmanın amacı, sosyal bilgiler öğretmenliği son sınıf öğretmen adaylarının mesleki gelişimlerine, öğretmenlik meslek etiği uygulamaları ile katkı sağlamaktır. Çalışma, 2019-2020 eğitim-öğretim yılının güz döneminde Türkiye’de bir devlet üniversitesinin eğitim fakültesinin sosyal bilgiler öğretmenliğin son sınıfta okuyan 55 öğretmen adayı ile gerçekleştirilmiştir. Araştırmada, nitel araştırma yöntemlerinden eylem araştırmasının bir türü olan school wide action research kullanılmıştır. Çalışmanın uygulama boyutunda araştırmacılar tarafından “öğretmenlik meslek etiği semineri”, 10 hafta boyunca yürütülmüştür. Çalışmada veri toplama aracı olarak araştırmacılar tarafından uzman görüşleri doğrultusunda geliştirilen soru formu kullanılmıştır. Toplanan veriler betimsel analiz yöntemi ile analiz edilmiştir. Araştırmanın sonuçlarını genel olarak değerlendirdiğimizde, öğretmenlik meslek etiği uygulamalarının öğretmen adaylarının meslek etik ilkelerine bakış açısını olumlu katkılar yaptığı, birey olarak mesleki, kişisel ve sosyal gelişimlerini arttırdığı, meslek etik ilkeleri konusunda sorumluluk hislerinin geliştirdiğini söylemek mümkündür. Bu doğrultuda öğretmen ve öğretmen adaylarının öğretmenlik meslek etiği ilkelerinin farkında olup bu ilkeleri benimseyip mesleklerinin gerektirdiği sorumlulukları almaya yöneltecek uygulamaların planlanması önerilebilir.
Sosyal Bilgiler Öğretmen Adaylarının Mesleki Gelişimine Bir Katkı: Öğretmenlik Meslek Etiği
Keywords: Other Fields of Education; Alan Eğitimleri